Enterprise Resource Planning and Internal Control Effectiveness - Chelsea Michelle Malau; Francis M. Hutabarat (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study aims to examine and analyze enterprise resource planning on internal control effectiveness in food and beverage companies. Enterprise Resource Planning (ERP) discussed in this study is the implementation of the ERP software in the company studied. In this study, internal control effectiveness is measured using Morris (2011) model and the model of Catalya and Hadiprajitno (2014). The population used in this research is food and beverage companies listed in Indonesia Stock Exchange (BEI). The technique of sample selection used purposive sampling. Based on these criteria, obtained samples as much as 14 companies during the observation period 2016-2017. In this sample there are 4 companies that are excluded from the study sample, because they have IPO after 2017. So, the final number of samples that can be observed as many as 28 samples. The analytical tool used in this study is the logistic regression. These results shows that the predictive ability of the regression model to project companies applying SPE by 100%. This study however states that enterprise resource planning implementation has no effect on internal control effectiveness in food and beverage companies. Nevertheless, the ERP implementation need to be socialized due to small number of companies implementing this software.